2016
DOI: 10.1371/journal.pone.0153671
|View full text |Cite
|
Sign up to set email alerts
|

Genome Wide Host Gene Expression Analysis in Chicken Lungs Infected with Avian Influenza Viruses

Abstract: The molecular pathogenesis of avian influenza infection varies greatly with individual bird species and virus strain. The molecular pathogenesis of the highly pathogenic avian influenza virus (HPAIV) or the low pathogenic avian influenza virus (LPAIV) infection in avian species remains poorly understood. Thus, global immune response of chickens infected with HPAI H5N1 (A/duck/India/02CA10/2011) and LPAI H9N2 (A/duck/India/249800/2010) viruses was studied using microarray to identify crucial host genetic compon… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
66
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 71 publications
(72 citation statements)
references
References 66 publications
6
66
0
Order By: Relevance
“…IL8L1 and IL8L2, CCL5 and SCYA4 vary with the subtype of AIV and infective dose. Although expression of XLC1, CCLi10 and CCL19 is upregulated in H5N1 or H9N2 infection in chickens or ducks , expression of XCL1, CCLi10 and CCL19 was not detected in DF‐1 cells infected with H5N1 and H9N2 AIVs. This may be because the complexity of the organism is far greater than that of a single cell type, and the host's immune system may be involved.…”
Section: Discussionmentioning
confidence: 92%
“…IL8L1 and IL8L2, CCL5 and SCYA4 vary with the subtype of AIV and infective dose. Although expression of XLC1, CCLi10 and CCL19 is upregulated in H5N1 or H9N2 infection in chickens or ducks , expression of XCL1, CCLi10 and CCL19 was not detected in DF‐1 cells infected with H5N1 and H9N2 AIVs. This may be because the complexity of the organism is far greater than that of a single cell type, and the host's immune system may be involved.…”
Section: Discussionmentioning
confidence: 92%
“…Conversely, the IFITM5 gene is down-regulated in the lung tissues following infection of chickens with LPAIV H9N2. It is suggested that this dysregulation of IFITM5 gene may contribute to the severity and the outcome of the influenza infection in chickens [120].…”
Section: Interferon-stimulated Genes (Isgs)mentioning
confidence: 99%
“…We then used this data to compare the expression of genes of interest in both Ross 308 and Ranger Classic (slow growing) broilers by PCR. Custom Agilent 4x44 K microarrays based on the V2 Chicken Gene Expression Array (Agilent Technologies), similar to those previously reported, were used for the microarray hybridization. Five samples each of healthy and infected birds were processed for hybridization using the Agilent Low Input Quick Amp Labelling protocol.…”
Section: Methodsmentioning
confidence: 99%